The Effectiveness of Use Short Stories to Improve The Students’ Vocabulary Mastery - Azisah, Riska; Sanjani, Alda; Asnidar, Anin (PROJECT (Professional Journal of English Education), 2025)
The purpose of this study was to determine the effectiveness of using short story media to improve students' vocabulary. With a pre-experimental using a single group pretest-posttest, the researcher employed quantitative research. The sample for this study consisted of 25 students’ from class VIII2 at UPTD SMPN 11 Barru. Purposive sampling was the method utilized to choose the study's sample. Following the exam, the researcher discovered that the students' average pretest score was 55.68 and their average posttest score was 69.6. The data was then evaluated using the t-test formula. With t-count = 9.14 and t-table = 2.068, the data analysis findings demonstrated that the t-count was greater than the t-table at a significance level of 0.05. It may be said that using short tales as a teaching tool greatly increases students' vocabularies.